2020
DOI: 10.1186/s12889-020-08601-z
|View full text |Cite
|
Sign up to set email alerts
|

HPV-based cervical cancer screening in Nicaragua: from testing to treatment

Abstract: Background: In Nicaragua, cervical cancer is the leading cause of cancer death among women. Human papillomavirus (HPV) testing, primarily using self-sampling, was introduced between 2014 and 2018 in three provinces. We analyzed data from the HPV screening program with the goal of describing key characteristics including reach, HPV prevalence, triage and treatment, and factors associated with follow-up completion. Methods: We analyzed individual-level data from routinely collected forms for women attending HPV-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The highest adherence rates were found in studies with direct referral to colposcopy, and/or intensive follow-up protocols (e.g., in Denmark HPV test results and follow-up recommendations were mailed to the women and their GPs). However, limited compliance to cytology triage has been reported among women with self-collected test from Argentina [ 13 , 21 ], France [ 19 ], Italy [ 29 ] and Nicaragua [ 20 ]. In a study carried out in France among non-attenders of low socio-economic level, 41% of women had a Pap smear after a positive HPV self-collected test [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest adherence rates were found in studies with direct referral to colposcopy, and/or intensive follow-up protocols (e.g., in Denmark HPV test results and follow-up recommendations were mailed to the women and their GPs). However, limited compliance to cytology triage has been reported among women with self-collected test from Argentina [ 13 , 21 ], France [ 19 ], Italy [ 29 ] and Nicaragua [ 20 ]. In a study carried out in France among non-attenders of low socio-economic level, 41% of women had a Pap smear after a positive HPV self-collected test [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in France among non-attenders of low socio-economic level, 41% of women had a Pap smear after a positive HPV self-collected test [ 19 ]. A study in Nicaragua carried out to analyse the key characteristics of an HPV-screening programme showed that 54% of women adhered to triage [ 20 ]. In Argentina, a study showed that 18% and 30% completed triage 60 and 120 days after a positive HPV result, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited compliance to triage has been reported in Argentina, 11,23,37,38 and other countries. [39][40][41] Studies that analyzed why screen-positive women failed to complete follow-up found that in most cases it was due to problems related to the health services organization [42][43] (i.e., delays or failures in result delivery, lack of appropriate guidance concerning the steps to follow after receiving a positive test, etc.). The EMA strategy is a complex intervention consisting of several steps that address multifaceted processes within interpersonal, organizational, and community contexts that may affected implementation delity.…”
Section: Discussionmentioning
confidence: 99%
“…However, adhering to triage and treatment can be challenging, especially among women with SC tests, who in general may not be regular health care system users, and therefore are at greater risk of not being able to continue with triage procedures. 10,11 In Argentina, clinician-collected screening involves taking two samples for HPV screening and Pap triage. Evidence has shown that women using SC have lower triage adherence.…”
Section: Introductionmentioning
confidence: 99%